Xylooligosaccharide production from sugarcane bagasse and leaf using Aspergillus versicolor endoxylanase and diluted acid - Forsan, Carolina Froes [UNESP]; de Freitas, Caroline [UNESP]; Masarin, Fernando [UNESP]; Brienzo, Michel [UNESP] (Springer Nature, 2021)
Xylooligosaccharides (XOS) are xylose oligomers that have numerous health benefits and can be produced by the acid or enzymatic hydrolysis of xylan-rich materials. This study aimed to extract xylan from sugarcane bagasse and leaf with 6% hydrogen peroxide in an alkaline medium and to hydrolyze it with Aspergillus versicolor endoxylanase and diluted acetic and sulfuric acids to produce XOS. The solubilization yields of xylan were 65.15% and 69.7% using sugarcane bagasse and leaf, respectively. The highest conversions of xylan from bagasse and leaf into XOS using acetic and sulfuric acids were 56.29% and 53.65%, and 40.16% and 45.37%, respectively. In enzymatic hydrolysis, the highest conversion yields were 67.43% and 69.71% for xylan from the bagasse and leaf, respectively. The results showed that acid and enzymatic hydrolysis resulted in high XOS yields; however, enzymatic hydrolysis of the degradation products did not occur.
Keywords: Acid hydrolysis; Biomass; Enzymatic hydrolysis; Xylan; Xylooligosaccharides